Depression, anxiety and stress among undergraduate students - Ranita Manap; Sohana Abdul Hamid; Marhaini Abdul Ghani (Penerbit Universiti Kebangsaan Malaysia, 2019)
The demands of living nowadays causing a rising number people being diagnosed with depression, anxiety or other mental health problems. A survey done by National Health and Morbidity 2015 finds that the prevalence of mental health problems among adults in Malaysia has increased from 10.7% in 1996, to 11.2% in 2006, to 29.2% in 2015. One in 10 individuals in 2011 to one in five in 2016 cases reported are among Malaysian students. This results reveal a worsening state of mental health problems especially among students in Malaysia that must be addressed. Therefore a preliminary study was conducted among students in one of the private college. The Depression, Anxiety and Stress Scale 21 (DASS-21) inventory was used to measure the students’ mental health based on three elements which are depression, anxiety and stress. The results showed that there are students having moderate to very severe level of depression, anxiety and moderate to severe level of stress. This finding is alarming in terms of increased risk for psychiatric morbidity because it indicates the amount of burden students have to bear in the current situation. Therefore, initiation of stress management programs such as expanding counselling activities, providing adequate facilities and resources should be highly prioritized by authorities. Interview sessions are suggested to explore in depth on these issues.